Rural Water Solutions - Howell, Jack (My University, 2014)
Billions of rural residents struggle to obtain adequate water supplies. Potential solutions must reflect cultural and physical differences. The purpose of this study was to highlight three responses that are effective, sustainable, and economically suitable. In parts of India, ultraviolet disinfection has proven to be an effective solution. In Nigeria, hand pumped wells have shown excellent results, but need to be coupled with rainwater collection systems to reduce the need to stand in long lines for water. In Argentina, rural villages have shallow wells that are becoming increasingly contaminated. A possible solution is a solar treatment system. By identifying the factors that account for a successful water system, this research can promote more widespread use of technologies that are both effective and culturally appropriate.
Color poster with text, maps, and images.
Keywords: Ultraviolet disinfection; Wells; Rural water supplies; Posters